Image Effect of Ambush Marketing: The Case of FIFA Soccer World Cup 2010 - Katharina Hutter; Uta Schwarz (Australian & New Zealand Marketing Academy (ANZMAC); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Ambush marketing is becoming a more and more relevant topic. However, most research has remained descriptive. No study has yet considered the image effects of ambush marketing using a causal model. Thus, the present paper provides a causal model of ambush marketing focusing on cognitive and affective image and their effects on downstream variables such as attitudes and purchase intention. The results of an online-survey with 278 respondents show that for typical sports brands affective image has a stronger impact on attitude towards the ambusher brand. In contrast, for atypical sport brands cognitive image has a stronger impact on the evaluation of the ambusher. Further, a strong impact of attitude towards the ambusher brand on purchase intention has been identified.
Conference: Proceedings of the Australian & New Zealand Marketing Academy (ANZMAC) 2012, December 3rd-5th, Adelaide, Australia
Keywords: M37; 650; Ambush marketing; Guerilla marketing; Image; PLS; Sport event; Ambush-Marketing; Guerilla-Marketing; Image; PLS; Sport event